Titans and olympians Greek & Roman myth (Myth and mankind., 1997)
The ancient Greeks and Romans created two of the most incredible and enduring cultures known to humanity. They also created a pantheon of gods and a rich body of mythology that has survived for centuries. Among these powerful myths is the story of Athena, the goddess of battle, who sprang from Zeus's head, and the story of Dionysus, the god of wine and fertility, whose worshippers achieved a state of mad ecstasy. These fantastic stories are captured in this volume.